Hukum Ekonomi Internasional: Tantangan dan Peluang bagi Indonesia dalam Era Globalisasi - Putri, Diva Safna; Faizal, Imam Afif; Estafania, Sella; Sapela, Annisa; Arasyidi, Umar; Siswajanthy, Farahdinny (Indonesian Journal Publisher, 2023)
International economic law is a branch of international law that regulates economic relations between countries. In the era of globalization, international economic law faces various challenges and opportunities that affect Indonesia as a developing country. The purpose of this article is to analyze the challenges and opportunities of international economic law for Indonesia, as well as to provide suggestions for developing a fairer and more inclusive international economic law. The method used is a literature study by reviewing various sources of information, such as journals, books, and reports. The results show that the challenges of international economic law for Indonesia include increased economic competition, the emergence of new trends in the global economy, and the existence of power imbalances between countries. The opportunities of international economic law for Indonesia include the great potential in the tourism sector, increased international cooperation, and the utilization of digital technology. The conclusion that can be drawn is that Indonesia needs to continue to adapt to the development of international economic law, as well as play an active role in contributing ideas and solutions to create a fairer and more inclusive international economic law.